Email subject lines and response rates to invitations to participate in a web survey and a face-to-face interview: the sound of silence - Sappleton, Natalie; Lourenço, Fernando (International journal of social research methodology, 2016)
This paper investigates the relationship between blank and non-blank email subject lines on levels of response to a solicitation to participate in an interview, and on participation in a web survey. Email use has grown substantially in recent years, presenting significant opportunity to the empiricist seeking research respondents. However, response to emails may be low because growth in the sheer volume of messages that individuals receive per day has led to a sense of 'email overload', and faced with the challenge of personal email management, many recipients choose to ignore some messages, or do not read them all fully. Drawing on information gap theory, we expected that sending an invitation with a blank subject line would induce a sense of curiosity in recipients that would improve email response and willingness to participate in research studies. However, findings from research with two samples with different propensities to participate in research (academics and business owners) revealed that an email invitation with a blank subject line does not increase overall response rates to a web survey and a face-to-face interview over either an informative subject line or a provocative subject line, but that it does prompt a greater number of active refusals. Based on this finding, recommendations for researchers are outlined.